Nepal’s 2025 Uprising: Geopolitical Entrapment, Neoliberal Failure, and Gen Z Activism - Santa Bahadur Thapa (International Journal of Humanities, Education, and Social Sciences, 2026)
This paper examines the Gen Z September 2025 movement in Nepal to explain how endemic corruption, deep socioeconomic disenchantment, and digitally native activism converged to generate an unprecedented wave of political change. It aims to analyze the movement’s rapid escalation, the constitutional “fault line” it exposed between revolutionary digital legitimacy and established constitutional legality, and the broader implications of this crisis in terms of regional contagion and governance instability. The study employs a mixed-methods approach combining qualitative textual analysis of geopolitical reporting with quantitative analysis of digital mobilization metrics. Empirical evidence includes data on digital participation, such as a Discord poll used to select a new Prime Minister, indicating that political authority was, in part, derived through digital channels. The findings suggest that the uprising was structurally shaped by the breakdown of neoliberal policies, entrenched high-level corruption, and the influence of external actors, including the United States through the MCC, India’s geopolitical influence, and the role of INGOs and EDPs, which collectively contributed to domestic instability through weak institutional ownership. The paper concludes that the movement precipitated the downfall of the government and triggered a constitutional crisis. Its contribution lies in highlighting how digital political legitimacy can destabilize conventional constitutional frameworks when combined with systemic corruption, external geopolitical pressures, and severe social inequality, thereby underscoring the need to move beyond revolution-era accountability toward deeper structural reforms addressing governance failures and the contradictions underlying violent instability.